Pathway from water-conflict to water-peace in the Middle East and North Africa - Khalifa, Muhammad; Al-Zu’bi, Maha; Brouziyne, Youssef (IWA Publishing, 2025)
The Middle East and North Africa (MENA) region, with its arid and semi-arid climate, faces profound challenges in managing limited water resources. These challenges are further intensified by political tensions and socioeconomic inequalities, often resulting in water being an essential element in conflicts and tensions. Particularly during the last decade, the number of conflicts involving water has increased dramatically in MENA. This research explores the dynamics of water’s role in conflicts, actors and scales of conflict across five fragile MENA countries, where it serves as a weapon, a catalyst, and a casualty. The analysis revealed a significant increase in the number of water-related incidents during the last two decades in these countries, with devastating implications on multiple social, economic, and security dimensions. The study suggests a concentric circle transformation (CCT) framework with three tiers of strategies: foundational, supportive, and expansive to help move from water-conflict to water-peace in MENA. These strategies, with examples of interventions, support transformation to water-peace by integrating soft interventions like empowering local communities, raising awareness, with hard interventions such as building resilient infrastructures and leveraging the power of innovative technological solutions. The framework offers scalable and adaptable solutions for regions facing similar challenges globally.